Representasi Pemilu bagi Para Penyandang Disabilitas dalam Dinamika Reparasi Politik Indonesia untuk Mendukung Demokrasi di Era Modern - Muhammad Irfan Setiawan; Thouf Salsabila; Millati Islamia Hanifa; Rahelda Meika Sinaga (Lembaga Pengembangan Kinerja Dosen, 2024)
Elections (Pemilu) represent a pivotal moment in democracy, where citizens exercise their right to vote and determine the nation's leadership and direction. Since the reform era, Indonesia has consistently held free and fair elections with increased civil participation. However, issues remain concerning the participation of people with disabilities, a group that often faces exclusion in political decision-making. Despite legal frameworks like Law No. 8 of 2016 ensuring the political rights of persons with disabilities, implementation in practice remains inadequate. This literature study examines the challenges faced by disabled voters, focusing on the lack of accessibility at polling stations and their underrepresentation in the voter registry. It highlights the urgency of political participation for persons with disabilities as a means to foster inclusive democracy and social change in Indonesia. Affirmative actions, such as the establishment of quotas and policies, are discussed as essential steps toward ensuring equal political rights for disabled individuals. Additionally, the role of technology in optimizing participation through programs like DIGI-EDVOT is explored. However, challenges remain due to unequal access and technological literacy among people with disabilities.